The institute of counter-security as a novelty of the reform of civil procedure law of Ukraine - Ханик-Посполітак, Роксолана Юріївна; Ханик-Посполітак, Р. Ю.; Ханик-Посполитак, Роксолана Юрьевна; Khanyk-Pospolitak, Roksolana Yu.; Ковальчук, Інна Сергіївна; Ковальчук, І. С.; Ковальчук, Инна Сергеевна; Kovalchuk, Inna S.; Билиця, Ігор Олегович; Билиця, І. О.; Былица, Игорь Олегович; Bylytsia, Ihor O.; et al. (Universidad de la Amazonia, 2020)
The article is dedicated to investigation of counter-security as a novelty of the reform of Ukrainian civil procedure legislation. The analysis of rules of the current procedural legislation on counter-security as a novelty of the civil process in Ukraine was made in the article. The determination of features of the institute of counter-security in the mechanism of civil proceedings was given. The role of counter-security in the civil process was identified. The conclusion was drawn that through the institute of counter-security, the principle of equality of parties is ensured, which is manifested in the equal assignment of the defendant to such procedural rights which are effectively identical to the rights of the plaintiff. Therefore, the defendant was granted effective protection against the claim by virtue of the new institute. It is stated that the counter-security should be seen as a way of preventing the plaintiff's abuse of procedural rights and offsetting the potential consequences. The introduction of counter-security is a clear step forward to European standards of quality and efficiency in the administration of justice, however, by examining civil procedural law and jurisprudence, the conclusion was made that the institution is not regulated at this stage of its establishment and application.

Статтю присвячено дослідженню зустрічного зaбeзпeчeння як новели реформи цивільного процесуального законодавства України. У статті здійснено аналіз норм чинного процесуального законодавства щодо зустрічного забезпечення як новели цивільного процесу в Україні. Було визначено особливості та порядок здійснення iнституту зустрічного забезпечення в мeхaнiзмi цивiльного процeсуaльного судочинствa. Було виявлено шляхи вдосконaлeння тa роль зустрічного забезпечення в цивiльному процeсі. Зроблено висновок, що через інститут зустрічного позову забезпечується виконання принципу рівності сторін, який проявляється у рівнозначному наділенні відповідача такими процесуальними правами, які за ефективністю є тотожними правам позивача. Отже, відповідач завдяки новелі отримав дієвий захист від забезпечення позову. Зустрічне забезпечення слід розглядати як спосіб перешкоджання зловживанню процесуальним правом з боку позивача та компенсацію можливих наслідків. Запровадження зустрічного забезпечення є безумовним кроком вперед до європейських стандартів якості та ефективності здійснення правосуддя, однак, здійснивши дослідження цивільного процесуально законодавства та судової практики, можна зробити висновок про недосконалість урегулювання зазначеного інститут на даному етапі його становлення та застосування.

Статья посвящена исследованию встречного обеспечения как новеллы реформы гражданского процессуального законодательства Украины. В статье осуществлен анализ норм действующего процессуального законодательства по встречному обеспечению как новеллы гражданского процесса в Украине. Были определены особенности и порядок осуществления института встречного обеспечения в мeхaнизме гражданского процeсуaльного судопроизводства. Установлено пути совершенствования и роль встречного обеспечения в гражданском процeссе. Сделан вывод, что через институт встречного иска обеспечивается выполнение принципа равенства сторон, который проявляется в равнозначном наделении ответчика такими процессуальными правами, которые по эффективности тождественны правам истца. Итак, ответчик благодаря новелле получил действенную защиту от обеспечения иска. Встречное обеспечение следует рассматривать как способ препятствования злоупотреблению процессуальным правом со стороны истца и компенсацию возможных последствий. Введение встречного обеспечения является безусловным шагом вперед к европейским стандартам качества и эффективности правосудия, однако, совершив исследования гражданского процессуально законодательства и судебной практики, можно сделать вывод о несовершенстве урегулирования указанного института на данном этапе его становления и применения.
Khanyk-Pospolitak R. The institute of counter-security as a novelty of the reform of civil procedure law of Ukraine / R. Khanyk-Pospolitak, I. Kovalchuk, I. Bylytsia // Amazonia Investiga. – V. 9(26). – Universidad de la Amazonia, 2020. – P. 28-35.
Keywords: сounter-security; injunction relief; abuse of law; justice; civil process; зустрічне забезпечення; забезпечення позову; зловживання правом; правосуддя; цивільний процес; встречное обеспечение; обеспечение иска; злоупотребление правом; правосудие; гражданский процесс; Research Subject Categories::LAW/JURISPRUDENCE::Procedural law::Civil procedure